Understanding the Resilience Process of Deaf Individuals Facing Accessibility Barriers: A Phenomenological Study - Muskinul Fuad; Laeli Linatussa'adah; Lutfi Faishol (Scidacplus, 2026)
Accessibility barriers remain a major challenge for Deaf Individuals in various aspects of life, including communication, education, public services, and social participation. Limited visual communication support, the lack of sign language interpreters, and low public awareness of Deaf culture often result in discrimination, social exclusion, and psychological distress. This study aims to explore the resilience process of Deaf Individuals in facing accessibility barriers within the Batir Isyarat Banjoemas Community, Banyumas Regency. The research employed a qualitative phenomenological approach involving five Deaf participants. Data were collected through in-depth interviews, observation, and documentation, then analyzed phenomenologically to identify the essence of participants' lived experiences. The findings reveal that resilience develops through a dynamic interaction between personal, relational, and social factors. Participants experienced communication barriers, limited access to information, and social stigma, which affected their emotional and psychological well-being. However, they demonstrated resilience through persistence, resistance, recovery, adaptation, and transformation. The resilience process was reflected in four major themes: experiences of Deafness and social stigma, psychological struggles, the development of coping strategies and resilience resources, and self-transformation toward identity acceptance and advocacy awareness. The Batir Isyarat Banjoemas Community played a significant role in providing social support, strengthening collective identity, and fostering empowerment among Deaf Individuals. These findings highlight that resilience among Deaf Individuals is not merely an individual capacity but a multisystemic process shaped by interactions with supportive environments.